A dataset of [68Ga]Ga-Pentixafor PET/CT images of patients with high-grade Glioma - Hessamoddin Roustaei; Nasim Norouzbeigi; Habibeh Vosoughi; Kamran Aryana (Data in Brief, 2023)
This paper contains single-center prospective information showing illustrative examples of chemokine receptor-4 (CXCR4) targeting in high-grade glial brain tumors in treatment-naïve adult patients using a novel radiolabeled PET tracer: [68Ga]Ga-CXCR4 PET/CT.High-grade glioma is one of the most resistant malignancies to treatment. Despite major breakthroughs in diagnostic and therapeutic approaches, the overall 5-year survival rate remains in the 5–10% range. CXCR4 is a chemokine with the C-X-C motif that is overexpressed in high-grade gliomas.The 24 consecutive treatment- naïve enrolled patients underwent PET/CT images using the SIEMENS scanner (Biograph6 TrueV) and received the radiotracer intravenously. After approximately 60 min, the PET/CT acquisition was performed with a dedicated scanner and in 10 min time per bed position. The images were reconstructed and analyzed with the 3D-OSEM algorithm, applying point spread function (PSF) or resolution recovery algorithm (TrueX in Syngo ® software, Siemens Medical Solution), 3 iterations, and 21 subsets using a 3 mm Gaussian post-smoothing filter.These data would be potentially beneficial for automatic tumor delineation machine learning after augmented with other data retrieved from different papers as well as for differentiation between an active viable tumor vs. post-surgery/necrosis in indeterminate cases. The theranostics potential (CXCR4-tageted labeled beta emitters) is one of the most novel areas of interest for future studies.